Controlled Deposition Of Electrospun Nanofibres Using Active Time-Varying Secondary Electrodes - Abdul Hamid, Nurfaizey; Akop, Mohd Zaid; Mohd Rosli, Mohd Afzanizam; Salim, Mohd Azli; Masripan, Nor Azmmi (Emerald Group Publishing Ltd., 2020)
Purpose – In this study, a new method of controlled deposition in electrospinning process is investigated using active time-varying secondary electrodes, in particular sine and triangular potentials to produce a wide and uniform electrospun fibre web. Design/methodology/approach – A special electrospinning setup was designed to include two independently charged secondary electrodes and a rotating collector. LabVIEW programme was used to control the applied potential at the electrodes. An aqueous solution of polyvinyl alcohol was used as the model material. An image analysis method was used to quantify the results. MATLAB programme was used to simulate the experimental results. Scanning electron microscope and SEM analyser software were used to examine the fibres. Findings – It was observed that when a time-varying electric potential was used, the electrospinning jet was periodically move to-and-fro in agreement with the varying electric field. The continuous movement of the jet expanded the width of the deposited web. The smooth oscillation of a sine wave potential was initially thought to produce a uniform pattern of deposited web; however, the results showed otherwise. A similar result was also found in simulations. The reason behind this observation was due to the difference in jet scanning speed between the two potentials. Originality/value – This study provides useful information for understanding how an active secondary electrode can be used as a new method of fibre deposition control in electrospinning process